Introduction. Visual Ethics after Communism - David Crowley (National Museum of the Romanian Peasant, 2021)
This special issue problematizes the often-uncritical use of images in publications and displays about communism. It poses a number of questions for anthropologists, historians, museologists and others: when does an image or a museum display present itself as problematic and for whom? Under what circumstances is it ethically justifiable to exhibit or publish such images or, conversely, to put images aside, leaving them undisplayed? When do arguments based on “the public good” outweigh the right to personal privacy, individual integrity and cultural patrimony of source communities?